Manual assembly design and planning in an augmented reality environment - Yan, Pang (2014)
Manual assembly design and planning includes two main issues: Product Design and Planning for assembly (PDP) and assembly Workplace Design and Planning (WDP). In order to improve the efficiency and quality of manual assembly design and planning activities, two issues are important: 1) an immersive and intuitive human-computer interface which allows the engineers designing and planning assemblies with sufficient information of the assembly environment in the early design stage; 2) the methodology to integrate the PDP and WDP processes in the immersive environment.